Search for Higgs Boson Production in Dilepton and Missing Energy Final States with 5.4 fb(-1) of p(p)over-bar Collisions at root s=1.96 TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Peters, K.; et al. (Amer Physical Soc, 2010)
A search for the standard model Higgs boson is presented using events with two charged leptons and large missing transverse energy selected from 5.4 fb(-1) of integrated luminosity in p ($) over bar collisions at root s = 1.96 TeV collected with the D0 detector at the Fermilab Tevatron collider. No significant excess of events above background predictions is found, and observed (expected) upper limits at 95% confidence level on the rate of Higgs boson production are derived that are a factor of 1.55 (1.36) above the predicted standard model cross section at m(H) = 165 GeV.